Restaurant food ordering method using NFC technology - Prashant Sangulagi; Sangamesh J Kalyane; Arvind M Bhavikatti; Shivpuje Pooja Sharad (Institute of Advanced Engineering and Science, 2022)
Mobile apps of various kinds continue to emerge as smartphones become more popular and mobile telecommunication matures. NFC is the most common wireless technology used in smartphones presently. It is used in mobile devices having built-in NFC to allow consumers to input payments, receive messages, and do nearer device recognition, among other things. The paper proposes the NFC technology-based food ordering system for all the customers who want to have food at their residence only. The results show that the application works properly in finding the nearby restaurants and completing the food order without any hustle.